Examining Talent Management Practices in a Canadian Not-for-Profit Context: A Theory-Driven Template Analysis - McCaig, Melanie; Rezania, Davar; Lightheart, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2022)
SummaryDespite significant interest in the field of talent management (TM), research has been largely confined to talent management in large corporations. Recent reviews have identified two significant gaps in the literature: 1) excessive focus on large for-profit organizations in North American, Asian and European private sectors; and 2) lack of consensus on TM definitions and activities in organizations. This article examines how TM is perceived and practised in a Canadian context. We used a theory-based approach and drew on previous conceptualizations of TM to examine the perspectives of 30 Canadian decision-makers. Using a conceptual model based on Bolander, Werr, and Asplund (2017), we observed that non-profit organization (NPO) decision-makers have a unique inclusive and competitive view of TM. Their view is defined predominantly by humanistic (acquired talent, inclusive, inputs and outputs) and competitive factors (recruitment dependence and skill development). They felt that talent should be inclusive and acquired, and many indicated that they were looking for people who could be trained. Their emphasis was on cultural fit, motivation and ability to grow intellectually and professionally, rather than on just acquiring the key skills needed for certain roles. The results indicate that TM is an organizational activity and needs to be understood and supported by the whole organization. Specifically, an inclusive view of TM requires adaptable organizational systems, such as collective agreements and accounting systems, which record how value is created in the organization. Future research could compare and contrast the views of those undertaking other functions in the organization, such as accounting, with the views of HR managers.AbstractWhile recognizing the importance of human capital in the success of non-profit organizations, existing research has primarily focused on talent management (TM) in large multinational organizations, mainly those in the private sectors of North America, Asia and Europe. In this article, we adopt a theory-driven approach and build on previous conceptualizations of TM to examine the perspectives of 30 Canadian nonprofit and for-profit decision-makers. Results show that Canadian decision-makers have a unique inclusive and competitive view of TM. Their view is defined predominantly by humanistic (acquired talent, inclusive, input and output) and competitive factors (reliance on recruitment and skill development). This study contributes a new perspective by providing empirical insights from managers of Canadian enterprises and pointing to implications for broader discussion, conceptualization and practice in the field.